Characterictics of ukrainian danube area surface water source mutagenicity with the use of microbial test-system Salmonella typhimurium ТА 98 - L. I. Kovalchuk; A. V. Моkiyenko; T. Yu. Vasiliyeva (Kazimierz Wielki University, 2015)
Коvalchuck L I, Моkiyenko A V, Vasiliyeva T Yu. Характеристика мутагенності води поверхневих водойм українського Придунав'я з використанням мікробної тест-системи Salmonella typhimurium ТА 98 = Characterictics of ukrainian danube area surface water source mutagenicity with the use of microbial test-system Salmonella typhimurium ТА 98. Journal of Education, Health and Sport. 2015;5(2):311-318. ISSN 2391-8306. DOI 10.5281/zenodo.17884 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A311-318 https://pbn.nauka.gov.pl/works/561488 http://dx.doi.org/10.5281/zenodo.17884 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.02.2015.   УДК 504.45(477.74):574.64:579   ХАРАКТЕРИСТИКА мутагенності ВОДИ поверхневих водойм Українського Придунав'я з використанням мікробної тест-сиСтемИ Salmonella typhimurium ТА 98 Characterictics of Ukrainian danube area surface water source mutagenicity with the use of microbial test-system Salmonella typhimurium ТА 98   1Л. Й. Ковальчук, 2А. В. Мокієнко, 3Т. Ю. Васильєва 1L I Коvalchuck, 2A V Моkiyenko, 3T Yu Vasiliyeva   1Одеський національний медичний університет, м. Одеса, 2ДП Український НДІ медицини транспорту МОЗ України, м. Одеса 3Одеський національний університет ім. І.І. Мєчнікова, м. Одеса 1Odessa National Medical University, Odessa 2State Enterprise Ukrainian research Institute foe Medicine of Transport of the Ministry of Health care of Ukraine, Odessa 3I. I. Mechnikov Оdessa national University, Odessa   Abstract The results of Ukrainian Danube area surface water sources mutagenicity with the use of microbial test-system Salmonella Typhimurium ТА 98 are shown in the work presented. The samples investigated cause different biological replies in the model bacterial Salmonella typhimurium ТА 98. This proves about variety of contaminants presenting in the water. The number of the samples caused the excess of mugagenecity spontaneous level (control indexes) more than a 100 of times constitutes 26.6 %; more than 50 times - 13.3 %; more than 10 times -  20.0 %; less than 10 times - 40.0 %. Taking into account the persisting character of           Ukrainian Danube area surface water sources contamination, it is necessary to continue the research of these sources mutagenicity with the use of bacterial test-system Salmonella typhimurium ТА 98. Key words: water, water object, mutagenicity, test-system Salmonella typhimurium TA 98, Ukrainian Danube area.   У роботі представлені результати досліджень мутагенності води поверхневих водойм Українського Придунав'я з використанням мікробної  тест-системи Salmonella typhimurium ТА 98. Досліджені проби викликають різноманітні біологічні відгуки в модельній бактеріальній системі  Salmonella typhimurium ТА 98, що свідчить про різноманіття забруднювачів, які знаходяться у воді.  Показано, що процент зразків води, які викликали перевищення спонтанного рівню мутагенезу (контрольні показники) більш ніж у 100 разів склав 26,6 %; більш ніж у 50 - 13,3 %; більш ніж у 10 -  20,0 %; менш ніж у 10 -  40,0 %. Тобто, має місце інтенсивне забруднення поверхневих водойм Українського Придунав'я речовинами-ксенобіотиками, які мають потужну мутагенну дію. Зважаючи на персистентний характер забруднення поверхневих водойм Українського Придунав'я, слід визнати за необхідне продовження досліджень мутагенності води цих водних об'єктів на бактеріальній тест-системі Salmonella typhimurium ТА 98. Ключові слова: вода, водні об'єкти, мутагенність, тест-система Salmonella typhimurium TA 98, Українське Придунав'я.   ХАРАКТЕРИСТИКА мутагенности ВОДЫ ПОВЕРХНОСТНЫХ ВОДОЕМОВ УКРАИНСКОГО Придунав'я С ИСПОЛЬЗОВАНИЕМ МИКРОБНОЙ  ТЕСТ-СИСТЕМЫ  Salmonella typhimurium ТА 98. В работе представлены результаты исследований мутагенности воды поверхностных водоемов Украинского Придунавья с использованием микробной  тест-системы Salmonella typhimurium ТА 98. Исследованные пробы вызывают различные биологические отклики в модельной бактериальной системе  Salmonella typhimurium ТА 98, что свидетельствует о многообразии загрязнителей, которые находятся в воде.  Показано, что процент образцов воды, которые вызвали превышение спонтанного уровня мутагенеза (контрольные показатели) более чем в 100 раз, составил 26,6 %; более чем в 50 - 13,3 %; более чем в 10 -  20,0 %; менее чем в 10 -  40,0 %.  То есть, имеет место интенсивное загрязнение поверхностных водоемов Украинского Придунавья веществами-ксенобиотиками, которые имеют мощное мутагенное действие.